2001
DOI: 10.1108/13673270110393266
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge codifiability, resources, and science‐based innovation

Abstract: Industry descriptions often depict science-driven industries as a single industry class, dominated by explicit knowledge in the form of patents, blueprints, diagrams, etc. This onedimensional view limits our ability to effectively manage the activities and routines across various stages of a science life cycle. The life cycle concept refers to the extent of development of the underlying scientific knowledge base. The knowledge in developed science fields (e.g. chemicals) is well codified, whereas in developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(71 citation statements)
references
References 28 publications
0
67
0
Order By: Relevance
“…However, the presumption in such an approach is that the knowledge is well codified (Cardinal et al, 2001). In convergence, this is more challenging, because such codification is initially limited.…”
Section: Convergent Innovation In Emerging Healthcare Technology Ecosmentioning
confidence: 99%
“…However, the presumption in such an approach is that the knowledge is well codified (Cardinal et al, 2001). In convergence, this is more challenging, because such codification is initially limited.…”
Section: Convergent Innovation In Emerging Healthcare Technology Ecosmentioning
confidence: 99%
“…It entails the latest item for consumption, the modern technology, the innovative marketplace (Chen et al, 2004). Similarly, in merchandise enlargement schedule innovation process include the scientific, objective, and comprehension base actions (Cardinal et al, 2001). From the literature it is observed that innovation is supported by KM that consist creation of new thoughts and proper utilization of organizational resources.…”
Section: Innovationmentioning
confidence: 99%
“…In research and development the attributes of explicit knowledge are powerful with wealthy substitute of tacit knowledge. It is essential for unions to assemble assets and facilities that will permit them to confine and codify knowledge and product development practices, to make certain knowledge transfer (Cardinal et al, 2001). The third important role is cooperate in innovation is to allow the teamwork.…”
Section: Nature and Role Of Km In Innovationmentioning
confidence: 99%
“…There are literally many studies on how to detect such factors (Alavi & Leidner, 1999;Cavusgil et al, 2003;Cardinal et al, 2001). Gupta and McDaniel (2002), for instance, investigated the link between the KM in contemporary firms and the development of a sustainable competitive advantage.…”
Section: Introductionmentioning
confidence: 99%